Preventing Noise and Vibration During the 60 Years of Activity of the Central Institute for Labour Protection – National Research Institute - ZAWIESKA, Wiktor Marek; PLEBAN, Dariusz (Archives of Acoustics, 2011)
In 2010, the Central Institute for Labour Protection – National Research Institute celebrated the 60th anniversary of its activity. Primary objectives of the Institute have been and continue to be the protection of employees against any hazards at work stations. Among the numerous hazards, vibroacoustic ones are becoming prevailing. Therefore, one can now dare to say that the 60 years of activity of the Central Institute for Labour Protection have also meant 60 years of preventing noise and vibration in the working environment. For those 60 years of activity, Central Institute for Labour Protection has been associated with outstanding acousticians and vibration specialists. The first chairperson of the Scientific Council of the Central Institute for Labour Protection was Professor Ignacy Malecki, one of the most outstanding Polish scientists. Chairpersons of the Council have also included Professor Adam Lipowczan and Professor Zbigniew Engel and the members of the Council have included Professor Stefan Ziemba and Professor Jerzy Sadowski. In 1956, the Institute established the Department of Vibration Research, further transformed into the Department of Technical Acoustics and since 1990 – the Department of Acoustic and Electromagnetic Hazards. The Department was founded and for a long time headed by Assistant Professor Czesław Puzyna. Following Professor Puzyna’s retirement, the Department was headed by Assistant Professor Danuta Augustynska. At present, it is the Department of Vibroacoustic Hazards, since 2007 headed by Dariusz Pleban, Ph.D., Eng.